Hypoglossal nerve tumor: A rare primary extracranial meningioma of the neck - Zulkiflee, Abu Bakar; Prepageran, Narayanan; Omar, Rahmat; Jayalakshmi, Pailoor; Sharizal, Tengku (SAGE Publications, 2012)
We report a case of primary extracranial meningioma arising from the hypoglossal nerve in a 54-year-old man who presented with a 9-month history of hoarseness and progressive dysphagia. He had also noticed that his tongue was deviated to the left and, as a result, he was having difficulty pronouncing words. Examination revealed fasciculation and muscle wasting on the left side of the tongue. Other cranial nerve functions were normal. Contrast-enhanced computed tomography detected a heterogeneous mass that had arisen above the bifurcation of the left common carotid artery and had extended to near the skull base. Transcervical excision of the tumor was performed, and histopathology identified it as a meningioma of the hypoglossal nerve. The patient recovered uneventfully, and he was without recurrence at more than 2 years of follow-up. A primary extracranial meningioma is extremely rare, and its presentation may be subtle. A thorough investigation is necessary to avoid fatal compressive symptoms. © 2012 Vendome Group, LLC.